Collaborative care skill training workshop: how Australian carers support a loved one with an eating disorder. (2nd January 2016) - Pépin, Geneviève; King, Ross
ABSTRACT: This study examined the impact of participating in the Collaborative Care Skill Training Workshops on carers' coping strategies, expressed emotion (EE), burden, distress, confidence in their loved one's capacity to change, as well as the previously unexplored dimension of accommodating and enabling of their loved one's eating disorder behaviour. A non-experimental research design was implemented and 77 carers from Victoria, Australia participated in the study and completed questionnaires at pre-and post-intervention and an 8-week follow-up. Significant reductions occurred in accommodation and enabling of some eating disorder behaviours, as well as in carers' maladaptive coping, EE, eating-disorder-specific burden and psychological distress. Increased confidence that their loved one could change was also observed. These changes were maintained at a follow-up. Results suggest that the workshop can be effective in decreasing carer use of maladaptive coping, carer distress and burden. Notably, it targets and had contributed to reducing factors associated with maintaining eating disorders such as accommodation and enabling of certain eating behaviours and high levels of EE. Modification to the content of the workshop may be required to improve carers' adaptive coping and reduce certain behaviours which accommodate and enable the eating disorder.